The Ottoman Turkish Expedition and the Anti-Colonialism Movement of the Sultanate of Aceh Darussalam 1530-1568 - Haykal, Muhammad (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
The appearance of the Portuguese fleet in the Indian Ocean and the Straits of Malacca was the starting factor for triggering colonialism in Nusantara. The emergence of the fleet which then continued to the domination of the Portuguese on the one hand had disrupted the expansion of the Ottoman Turks who had controlled Egypt and the Arabian Penisula. On the other hand, it was also the main factor that encouraged the emergence and development of the Aceh Darussalam Sultanate as a resistance movement or anti-colonialism against the Portuguese. This article will examine how the emergence of the Portuguese in the Indian waters and the Malacca Strait has become the main driver for the emergence of the anti-colonialism movement initiated by the Sultanate of Aceh. As well as the author continues by concluding that it was the the anti-colonialism movement became the main factor in establishing the relationship between the Aceh Darussalam Sultanate and the Ottoman Turks. However, this was because the Ottoman Turks also had the same interests as Aceh, namely against Portuguese domination in the Indian Ocean. To Ensure their trade flocks and Hajj route safe. The conclusion obtained is that the domination of the Portuguese in the Indian Ocean and the Straits of Malacca has indirectly become the main factor in the realization of military and even economic cooperation relations between the two Islamic empires. This paper is a research of literature and historiography using a narrative descriptive method, presenting history in combination with chronology and correlations between each event.